2020
DOI: 10.3389/fmicb.2020.596372
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic AMP Receptor Protein, Crp, Is Required for the Decolorization of Acid Yellow 36 in Shewanella putrefaciens CN32

Abstract: Shewanella shows good application potentials in the decolorization and detoxification of azo dye wastewater. However, the molecular mechanism of decolorization is still lacking. In this study, it was found that Shewanella putrefaciens CN32 exhibited good decolorization ability to various azo dyes, and a global regulatory protein cAMP receptor protein (Crp) was identified to be required for the decolorization of acid yellow 36 (AY) by constructing a transposon mutant library. Then, the molecular mechanism of AY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Next, a second centrifugation was performed, and the pellet was discarded; the absorbance of the supernatant at 534 nm (A 534 ) was measured in a cuvette. The anaerobic fermentation procedure was modified from that of Liu et al (2020). Briefly, Serratia sp.…”
Section: Prodigiosin Production and Yield Analysismentioning
confidence: 99%
“…Next, a second centrifugation was performed, and the pellet was discarded; the absorbance of the supernatant at 534 nm (A 534 ) was measured in a cuvette. The anaerobic fermentation procedure was modified from that of Liu et al (2020). Briefly, Serratia sp.…”
Section: Prodigiosin Production and Yield Analysismentioning
confidence: 99%
“…As a cellular secretion, riboflavin has been proved in many studies to be involved in extracellular electron transfer processes ( Song et al, 2019 ; He et al, 2020 ; Wang J. H. et al, 2020 ). Liu et al’s (2020d) study showed that 2 μM riboflavin as an electron shuttle significantly promoted the decolorization efficiency of Shewanella putrefaciens CN32 wild-type to the dye acid yellow 36; Ramos-Ruiz et al (2016) observed that riboflavin increased the reduction efficiency of anaerobic granular sludge system to tellurate by 11 times, and further studies found that the inhibition of anaerobic methanogenic activity by tellurate was mitigated by adding riboflavin to the UASB reactor, with the COD removal rate of the riboflavin-added reactor increasing by 4.6 times higher than that of the reactor without riboflavin addition ( Ramos-Ruiz et al, 2017 ).…”
Section: Introduction To Electron Shuttlementioning
confidence: 99%